Pancasila dan Penguatan Hukum Tata Negara dalam Era Demokrasi: Pancasila and Strengthening Constitutional Law in the Democratic Era - Ahmad Muhammad Mustain Nasoha; Muhammad Keizafa Yusuf Agachi; Marshal Ruhul Muhammad; Muhammad Bima Apriyandi; Rafi Romadoni (Litera Academica Publishing, 2024)
This journal examines how Pancasila values—such as social justice, people’s sovereignty, and unity can remain relevant and dominant within the framework of constitutional law amid various dynamics of democracy and globalization. One of the main issues discussed is the concern that legal and political practices in the democratic era often deviate from Pancasila values, as seen in various cases of injustice, abuse of power, and social disintegration. The journal also highlights the influence of globalization on Indonesia’s legal system, where international standards on human rights, democracy, and the rule of law demand adaptation within national laws. However, this adaptation must be carried out while maintaining a national identity rooted in Pancasila. Therefore, it is crucial to find a balance between adjusting to global demands and upholding Pancasila values in constitutional law. The writing of this journal is driven by the urgent need to reassess the relevance of Pancasila in constitutional law, especially in facing new challenges such as uncontrolled freedom, rising individualism, and the threat of social disintegration. This journal offers solutions to strengthen Pancasila’s role as the foundation of constitutional law through the reaffirmation of its principles in legal and political policies. Through this study, it is expected to make a significant scholarly contribution in preserving and sustaining Pancasila as the foundation of the state and law in Indonesia, and ensuring that Indonesia’s constitutional law continues to reflect national values in the era of democracy and globalization.